MILITARY DECISION-MAKING SUPPORT SYSTEMS BASED ON GEOGRAPHIC INFORMATION SYSTEMS TECHNOLOGIES - Писаренко, Р. (Київський національний університет імені Тараса Шевченка, 2022)
The sharp increase, circulation, accumulation by organizations of large enough volumes of spatial data used in geographic information systems to solve problems of updating and creating maps, require systematization and proper use, the task of systematization, processing and visualization of geodata for geographic information systems tactical level. Using the capabilities of GIS in the processing of geodatabases to obtain the necessary information, in turn, increases the efficiency of decision-making. This article is devoted to the development of requirements for the construction and operation of a geographic information system of the tactical level. The functional structure of the GIS of the tactical level of the Armed Forces of Ukraine is determined by the list of basic functions that this system implements. In addition, functionally, depending on the scope and content of GIS tasks is divided into two levels: operational and tactical, tactical. In turn, at each of the defined levels of the system, the common main functions implemented by GIS are: data entry and updating; data storage and retrieval; data analysis; output and presentation of data and results. Based on this GIS tactical level of the Armed Forces of Ukraine functionally consists of four subsystems: data collection, input and updating; data storage and retrieval; data analysis; output and presentation of data and results. At present, the topographic service of the tactical unit is not able to fully provide the lower level headquarters with electronic maps and prepare a detailed analysis of the necessary properties of the area. The use of information technology in the tactical chain of command of troops and weapons is possible only after improving the technical and organizational components of the topographic service of the connection. A significant step towards increasing the efficiency of geospatial data use and simplifying access to them is the implementation of portal solutions at the level of the Armed Forces of Ukraine.

Різке збільшення, циркуляція, накопичення організаціями достатньо великих обсягів просторових даних, які використовуються в геоінформаційних системах для вирішення завдань оновлення та створення карт, потребують систематизації і правильного їхнього використання, постає задача систематизації, обробки та візуалізації представлених геоданих для геоінформаційних систем тактичного рівня. Використання можливостей ГІС при обробці даних баз геоданих для отримання необхідної інформації підвищує ефективність прийняття рішення. Розглянуто розробку вимог щодо побудови та функціонування геоінформаційної системи тактичного рівня. Функціональна структура ГІС тактичного рівня ЗС України визначається переліком основних функцій, які реалізує ця система. Залежно від обсягу та змісту завдань функціонально ГІС розподілено на два рівні: оперативно-тактичний, тактичний, на кожному з яких загальними основними функціями, які реалізуються ГІС є: введення й оновлення даних; зберігання і пошук даних; аналіз даних; виведення та подання даних і результатів. ГІС тактичного рівня ЗС України функціонально складається з чотирьох підсистем: збору, введення та оновлення даних; зберігання та пошуку даних; аналізу даних; виведення та подання даних і результатів. На сьогодні топографічна служба тактичної ланки не спроможна в повному обсязі забезпечити штаби нижчого рівня електронними картами та підготувати детальний аналіз необхідних властивостей місцевості. Застосування інформаційних технологій у тактичній ланці управління військами та зброєю можливе тільки після вдосконалення технічної та організаційної складових топографічної служби з'єднання. Значним кроком в напрямі збільшення ефективності використання геопросторових даних і спрощення доступу до них є впровадження портальних рішень на рівні ЗСУ.
ОПЕРАТИВНІ ТА ТАКТИЧНІ ВИМОГИ ЩОДО ПОБУДОВИ ТА ФУНКЦІОНУВАННЯ ГЕОІНФОРМАЦІЙНОЇ СИСТЕМИ ТАКТИЧНОГО РІВНЯ
Keywords: geographic information system; geospatial support; geospatial data; геоінформаційна система; геопросторова підтримка; геопросторові дані